Understanding project management skills and insights for successful project delivery - Straw, Gary (Kogan Page, 2015)
Contents; Preface; Acknowledgements; Part One Projects in an ideal world; 01 An introduction to projects and project management; Learning outcomes; Introduction; Projects - initial perspectives; The project manager and project management; Project management is risk management; Project processes; Projects and lifecycles; Projects and gates; Projects: ingredients and early insights; Projects are complex; stakeholders; change; Summary; Notes; References; 02 Projects at the conceptual phase; Learning outcomes; Introduction; Conceptual phase; Entry points; Some important questions